2018
DOI: 10.5539/ies.v11n11p109
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Development of Podcasting as a Technological Tool in Secondary Education in Greece: A Case Study

Abstract: The main objective of this study is to explore how podcasting can be implemented as a supportive technological tool in teaching English as a Second Language. To this aim, the field experiment research was conducted. The study was carried out in a total of 28 pupils of the first grade of high school at an educational institution on Rhodes, Greece in December 2017. The students were assigned into the experimental group (15 students) and the control group (13 students). A statistically significant difference has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thanks to its diverse contents, a podcast can draw students' interest as a digital tool for language learning. The quantity of podcast content positively affects students' motivation (Nikolou & Darra, 2018). Participant 2 stated: "Podcasts have become a very good approach for improving our English.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to its diverse contents, a podcast can draw students' interest as a digital tool for language learning. The quantity of podcast content positively affects students' motivation (Nikolou & Darra, 2018). Participant 2 stated: "Podcasts have become a very good approach for improving our English.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of contents found in podcast has a good impact on students' motivation. Nikolou and Darra (2018) interviewed 28 EFL pupils to conduct a quantitative research about the use of podcast. They concluded that podcast is interesting for the students and it allows them to interact in English with others in the classroom.…”
Section: The Effect Of Podcast In Improving the Students' Motivation mentioning
confidence: 99%
“…Furthermore, teachers can choose a content which is proper for the students' ability. Nikolou and Darra (2018) found that students expressed that the content on podcast is interesting and helpful. It is also confirmed by a questionnaire research conducted by Farshi (2013) who concluded that learners felt that podcast contents help them to be more motivated in language learning.…”
Section: The Effect Of Podcast In Improving the Students' Motivation mentioning
confidence: 99%
“…In this chapter student researchers and their lecturer describe a learning and teaching intervention where they used a sonic or sound-based approach, in this case podcasts, to assist in cultivating a nuanced approach for reading and understanding academic articles relating to Ethnomusicology themes. Although there are several studies on language development (Abdi & Makiabadi, 2019;Edirisingha et al, 2007;Nikolou & Darra, 2018) and listening skills expansion (Davydenko, 2021;Gonulal, 2020;Mirza Suzani, 2021) through podcasting, this intervention was aimed at developing specific academic literacy rather than general language skills. Podcasts play an important role in content dissemination and knowledge production at Rhodes University, and specifically at the International Library of African Music (ILAM) where the goals of the institute include community engagement and community-based education.…”
Section: Introductionmentioning
confidence: 99%